THE ROLE OF DIVERGENT AND CONVERGENT THINKING IN DEVELOPING INTUITIVE COMPETENCE OF CADETS (ON THE EXAMPLE OF HIGHER MATHEMATICS EDUCATION) (Web of Teachers: Inderscience Research, 2026)
This study investigates the pedagogical potential of divergent and convergent thinking strategies in developing intuitive competence among cadets within higher mathematics education in military institutions. The research applies problem-based learning, mathematical modeling, and real operational scenarios to foster multi-perspective analysis and optimal decision-making skills. The results demonstrate that divergent thinking enhances cognitive flexibility and hypothesis generation, while convergent thinking strengthens analytical precision and solution efficiency. Their integration significantly contributes to the formation of professional intuition, rapid reasoning, and operational readiness of future officers.